Ácidos grasos omega-3 en gestantes y síntomas depresivos en el postparto - Álvarez Ramírez, Miriam (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
Postpartum depression (PPD) is characterized by lacking of women’s interest in living during the puerperium. Its worldwide prevalence reaches 10-15% worldwide and 9-22% in Mexico; although this data have not been determined in Michoacan. PPD has a multifactorial etiology. Different nutritional factors have been associated with PPD, among them, the depletion of omega-3 fatty acids during pregnancy, especially docosahexaenoic acid (DHA) has been considered a risk factor for PPD. Besides, PPD diagnosis is underestimated, thus, frequently PPD is not treated, even though it can importantly affect the mother and child health. Objective. To establish the effect of dietary supplementation of DHA in the presence and magnitude of postpartum depressive symptoms (DS) in the presence or absence of risk of postpartum depression (RPD). Method. Quasi-experimental, comparative and longitudinal study. N=145 healthy pregnant women were allotted to 2 groups, either with or without RPD, according to their Postpartum Depression Predictors Inventory score. Both groups were supplemented with fish oil capsules (324 mg DHA/d) for 6 months. Quality and quantity of dietetic fatty acids were assessed by a Food Frequency Questionnaire. DS were detected at three different times: 20th week of pregnancy, 2nd week postpartum and 3rd month postpartum by the Edinburgh Postnatal Depression Scale (EPDS). Venous blood samples, before (20th week of pregnancy) and after supplementation, besides breast milk samples (3rd month postpartum), were taken in order to determine their lipid concentrations, by gas chromatography. Statistical analysis: Chi-squared test, Mann-Whitney U test, Wilcoxon test and Spearman correlation coefficient. Results. The percentage of women with postpartum DS decreased, as well as the EPDS score at three months postpartum in the group with RPD (p=0.006 and p=0.008 respectively). Eighty percent of the sample showed insufficient EPA and DHA dietary intake. Omega-3 fatty acids intake was: DHA 70 mg/d, EPA 30 mg/d, ALA 980 mg/d. Erythrocyte DHA increased after supplementation in both groups (with RDP p=0.008; Without RDP p<0.001).

La depresión postparto (DPP) se caracteriza por un desinterés en la vida de mujeres en puerperio. A nivel mundial tiene una frecuencia de 10-15% y en México una prevalencia de 9-22%, mientras que en Michoacán no existen reportes. Su etiología es multifactorial. Se han asociado a ella factores nutricionales como la depleción materna de ácidos grasos omega-3, especialmente el ácido docosahexaenoico (DHA). Su diagnóstico está subestimado y el no tratar esta patología afecta a la salud del binomio madre-hijo. Objetivo. Establecer el efecto de la suplementación dietética de DHA en la presencia y magnitud de los síntomas depresivos (SD) en el postparto, ante la presencia o ausencia del riesgo de depresión postparto (RDP). Metodología. Estudio cuasiexperimental, comparativo y longitudinal. N=145 mujeres embarazadas sanas, divididas en dos grupos, por medio del Inventario de Predictores de Depresión Postparto: con y sin RDP. Ambos grupos recibieron cápsulas de aceite de pescado (324 mg de DHA/d) por 6 meses. Se evaluó la calidad y cantidad dietética de la grasa ingerida por medio del Cuestionario de Frecuencia de Consumo de Alimentos. Se detectaron los SD en tres momentos: segunda mitad de embarazo, primeras semanas postparto y tres meses postparto, por medio de la Escala de Depresión Postnatal de Edimburgo (EPDS). Se tomaron muestras de sangre antes (embarazo) y después de la suplementación, además de muestras de leche materna (3er mes postparto), para medir sus concentraciones lipídicas por cromatografía gas-líquido. Análisis estadístico: Chi-cuadrada, U de Mann-Whitney, Test de Wilcoxon y Correlación de Spearman. Resultados. Disminuyó el porcentaje de mujeres con SD, así como la puntuación de EPDS, a los tres meses postparto en el grupo con RDP (p=0.006 y p=0.008, respectivamente). El 80% de la muestra presentó insuficiencia dietética para EPA y DHA. Su consumo fue de: 70 mg DHA/d y 30 mg EPA/d.
Facultad de Ciencias Médicas y Biológicas. Maestría en Ciencias de la Salud
Keywords: info:eu-repo/classification/cti/3; FCMB-R-M-2015-1421; Puerperio; Depresión postparto; Embarazo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2969